Reinvigorating primary school science through school-community partnerships - Rennie, Leonie; Wallace, J.; Venville, G. (2018)
© Springer International Publishing AG, part of Springer Nature 2018. All rights reserved. Many primary school teachers, when supported by opportunities that assist them to reframe their thinking about the nature of science, appear to demonstrate a capacity to willingly use new perspectives to reconsider science learning and teaching. In particular the need for science to be explored as a human endeavour and the need to generate for students reason to seek understanding, to make sense of and communicate thinking about phenomena and experiences. To this end primary teachers value science learning situated within experiences that are personally meaningful and contextually relevant to their students, often producing opportunities to invite perspectives and achievements from sources outside the school to broaden science learning beyond the confines of the classroom. When established effectively such partnerships can potentially enable students to engage in and develop an understanding of science as a process of investigation and collaboration dependent upon the social construction of knowledge. Through an exploration of three case studies, we demonstrate situations where primary teachers and schools intentionally take steps to ensure their students have a sense of connectedness to their local community and environment by developing mutually beneficial learning relationships with both formal and informal science partners. By doing so these schools actively broaden the primary school science curriculum to include aspects of contemporary science with a particularly strong emphasis on social and emotional aspects of learning. The result is a wider range of learning outcomes than were ever intended or anticipated for students, teachers and the community in general. Finally, the chapter identifies the characteristics that make school-community partnerships educationally valuable for science learning and teaching.